A direct absorption solar collector based on a water-ethylene glycol based nanofluid with anti-freeze property and excellent dispersion stability. (April 2019) - Xu, Xinxin; Xu, Chao; Liu, Jian; Fang, Xiaoming; Zhang, Zhengguo
Abstract: Herein a direct absorption solar collector (DASC) with the reduced graphene oxide (RGO)/water-ethylene glycol (EG) nanofluid as the working fluid was firstly explored. The RGO/water-EG nanofluid was prepared from a GO/water-EG nanofluid at a loading of 0.06% via the UV irradiation for 240 s. It is shown that the zeta potential of the RGO/water-EG nanofluid increases with temperature, suggesting its excellent dispersion stability at elevated temperatures. The base liquid consisting EG and water endows the nanofluid with anti-freeze property, making its DASC can be applied in cold weather. The RGO/water-EG nanofluid exhibited better optical absorption property and thermal conductivity than the previously reported RGO/water nanofluid. After being exposed under a solar intensity of 1000 W/m 2 for 6000 s, the temperature increase of RGO/water-EG nanofluid increases by 76.9% and the receiver efficiency increases by 70%, as compared to the base fluid. These good characteristics make RGO/water-EG nanofluid promising working fluid for DASCs. Consequently, a numerical simulation was employed to study the DASC based on the nanofluid with the liquid heights varying from 2 to 10 cm. It is revealed that the DASC based on the RGO/water-EG nanofluid exhibits good photo-thermal conversion performance and receiver efficiency, thus showing great potential in practical applications. Highlights: The dispersion stability of RGO/water-EG nanofluids increased with temperature. The RGO/water-EG nanofluids can be employed at temperatures as low as −47 °C. Compared to base fluid, RGO nanofluids exhibit increased temperature increments. Increases in receiver efficiency by 67%–70% is found for the optimal RGO nanofluid. The receiver based on the RGO nanofluid was experimentally and numerically studied.